Intelligent wound dressing with photo-thermal drug controlled release and motion sensing monitoring functions and preparation method thereof
By loading curcumin and lauric acid in wound dressings and using liquid metal circuits for photothermal controlled release and motion monitoring, the problem of lack of motion monitoring in existing dressings in active wound treatment is solved, and the promotion of wound healing is achieved and real-time monitoring of motion status.
Patent Information
- Application Number
- CN202411608621.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-12
- Publication Date
- 2025-02-21
AI Technical Summary
Existing wound dressings lack effective exercise monitoring functions when dealing with active wounds, resulting in the wound being overstretched during exercise, which in turn affects the healing process.
Smart wound dressings that realize drug controlled release and motion sensing monitoring functions by loading curcumin and phase change material lauric acid on the nanofiber membrane and printing liquid metal in situ in the double-layer nanofiber membrane as photothermal agents and flexible circuits, achieving intelligent wound dressings that control drug release and motion sensing monitoring functions .
Real-time monitoring of the movement status at the wound is achieved, and curcumin is controlled to release it through photothermal effect to promote wound healing, while improving the antibacterial, anti-inflammatory and antioxidant abilities of the dressing.
Smart Images

Figure CN119488625A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of wound dressings and the field of flexible strain sensors, and in particular relates to an intelligent wound dressing having both photothermal drug controlled release and motion monitoring functions and a preparation method thereof. Background Art
[0002] The skin is the largest tissue organ in the human body and is the body's first line of defense against pathogens, physical, chemical, and mechanical attacks. Since the skin is the interface between the internal and external environments of the body, long-term exposure to the external environment makes it more susceptible to external factors and faces a variety of damage threats and challenges. Common skin injuries include mechanical trauma, chemical burns, and skin ulcers caused by chronic diseases. These injuries not only lead to the loss of skin barrier function, but may also cause problems such as wound infection, inflammation, and excessive exudation of tissue fluid, which not only affects the wound healing rate, but also causes secondary damage to the patient, increasing the patient's treatment and psychological burden.
[0003] With the further development of skin tissue engineering, the development of wound dressings has become one of the key development directions in this field. Wound healing is a complex physiological process, including four overlapping stages: hemostasis, inflammation, proliferation and remodeling. In order to promote wound healing and prevent secondary damage to the wound by external factors, it is necessary to use appropriate dressings to treat the wound. Traditional gauze dressings can protect the wound from contamination and secondary mechanical trauma, and play a temporary shielding role. However, such wound dressings lack antibacterial and anti-inflammatory functions, cannot resist the infection of external microorganisms and remove inflammatory factors from the wound, and have no effect on wound healing. Ideal wound dressings should have multifunctional properties such as antibacterial, anti-inflammatory and cell proliferation. At present, the types of wound dressings are increasing, and common multifunctional wound dressings include sponges, hydrogels and nanofiber membranes. These multifunctional dressings combine a variety of different bioactive materials or drugs to give the dressings antibacterial, anti-inflammatory and other properties, accelerating wound healing. The development of multifunctional wound dressings fundamentally solves the problem that traditional gauze dressings have no effect on promoting wound healing and lack of protection against wound infection.
[0004] Although dressings with functional properties such as antibacterial properties have shown good potential in promoting wound healing, such dressings are not suitable for wound treatment in all parts, such as active wounds. In particular, when patients have insufficient perception of the active part of the wound, secondary injury may occur. For example, in patients with diabetes, the wound surface lacks normal sensory motor response due to nerve necrosis; for example, patients with hemiplegia, paralysis or elderly people with limited mobility often cannot actively control limb movement due to motor nerve damage. If not controlled in time, these wounds may further deteriorate and develop into chronic wounds. In addition, during the treatment process, abuse or misuse of therapeutic drugs often leads to increased drug resistance of pathogens and recurrence of old diseases. At present, dressings for active skin wounds are mainly reflected in the improvement of dressing elasticity. Compared with ordinary multifunctional dressings, high-elastic dressings can buffer the stretching of wounds at joints during movement to a certain extent and reduce damage to new skin tissue. However, existing wound dressings can only buffer movement stretching within a certain range, and their ability to protect wounds is limited. During the active wound treatment stage, if real-time monitoring of wound movement can be achieved and the movement amplitude of the wound can be converted into an easily identifiable electrical signal for evaluating the amplitude of movement, it will be crucial to avoid wound deterioration caused by large-scale wound stretching. In addition, even if the patient has a large-scale wound stretching without realizing it, the intelligent monitoring system can promptly notify the patient and his or her caregiver, thereby effectively intervening in the wound and reducing secondary damage to the wound caused by movement and stretching. Therefore, in a multifunctional wound dressing that has antibacterial and anti-inflammatory properties, integrating an intelligent motion monitoring system to monitor the movement status of the wound in real time is of great significance for the treatment of dynamic wounds such as skin wounds at joints. Summary of the invention
[0005] In view of this, the present invention provides an intelligent wound dressing with both photothermal drug controlled release and motion sensing monitoring functions. The wound dressing provided by the present invention loads the drug curcumin and the phase change material lauric acid onto the surface of the nanofiber membrane prepared by electrostatic spinning through electrostatic spraying technology, and at the same time, liquid metal is in situ printed in the double-layer nanofiber membrane to act as a photothermal agent and a flexible circuit to achieve the controlled release of curcumin to treat wounds through the photothermal effect, while also being able to monitor the movement state of the wound at the joint in real time.
[0006] Another object of the present invention is to provide a method for preparing an intelligent wound dressing having both photothermal drug controlled release and motion sensing monitoring functions.
[0007] To this end, the first technical solution provided by the present invention is as follows:
[0008] An intelligent wound dressing with both drug controlled release and motion detection functions is composed of a base material, a photothermal agent and a sensor flexible agent liquid metal, a drug-carrying phase change material lauric acid, and an active component curcumin.
[0009] Furthermore, in the above-mentioned intelligent wound dressing having both drug controlled release and motion detection functions, the base material is thermoplastic polyurethane.
[0010] Among them: Each substance is abbreviated as follows:
[0011] Thermoplastic polyurethane (TPU), liquid metal (LM), lauric acid (LA) and curcumin (CUR).
[0012] Furthermore, in the above-mentioned intelligent wound dressing with both drug controlled release and motion detection functions, the liquid metal is eutectic gallium indium with a purity of 99.999%, wherein the gallium content is 75wt% and the In content is 25wt%.
[0013] Furthermore, in the above-mentioned intelligent wound dressing having both drug controlled release and motion detection functions, the mass ratio of the base material, lauric acid and curcumin is 75-225:50-150:2.5-7.5.
[0014] The second technical solution provided by the present invention is as follows:
[0015] S1: electrospinning the TPU spinning solution to obtain a TPU nanofiber membrane, and cutting it into two pieces of the same size for standby use;
[0016] S2: A Peano pattern is printed on one of the TPU nanofiber membranes prepared in S1 through an in-situ template, and liquid metal is filled in the hollow part of the Peano pattern to obtain a TPU nanofiber membrane with a flexible circuit;
[0017] S3: Another piece of TPU nanofiber membrane prepared in S1 was bonded to the TPU nanofiber membrane with flexible circuit prepared in S2 printed with liquid metal surface by electrospinning to obtain a flexible strain sensor layer, named TPU@LM;
[0018] S4: The curcumin / lauric acid solution is bonded to the TPU@LM prepared in S2 by electrostatic spraying to obtain the primary product TPU@LM@CUR;
[0019] Step 5: With the liquid metal circuit Peano pattern as the center, the TPU@LM@CUR prepared in S4 is cut to obtain the finished smart wound dressing TPU@LM@CUR. In the present invention, the preparation method of the TPU spinning solution is: weigh TPU and add it to the hexafluoroisopropanol solution, stir it under the condition of magnetic stirring, the stirring speed is 300-400rpm, the stirring time is 6-12h, and the final TPU spinning solution concentration is 15% (w / v);
[0020] In the present invention, the electrospinning process of the TPU nanofiber membrane in step 1 is: first, the TPU spinning solution is sucked into a 5mL syringe, and then the syringe is installed on the syringe pump, and the spinning speed is adjusted to 1.5mL / h. Take a piece of silicone oil paper and stick the silicone oil paper on a metal collection plate. Finally, turn on the high-voltage DC power supply, adjust the voltage to 18-19kV, and start spinning. The needle is 15cm away from the collection plate, and the collection is carried out for 2.5h to obtain the TPU nanofiber membrane, and it is cut into two pieces of TPU nanofiber membrane of the same size for subsequent use;
[0021] Next, a Peano pattern was cut out on the PVC board using a cutting machine as an in-situ stencil printing template, and the in-situ stencil printing template was placed on top of one of the TPU nanofiber membranes prepared above, and liquid metal was in-situ stencil printed to prepare a liquid metal flexible circuit layer.
[0022] S3: Another piece of TPU nanofiber membrane (as the second layer of TPU nanofiber membrane) is combined with the side coated with liquid metal to finally obtain a flexible strain sensor layer, named TPU@LM. Subsequently, TPU@LM is placed in a vacuum oven and dried at room temperature under vacuum conditions for 12 hours;
[0023] In the present invention, the preparation method of the curcumin / lauric acid solution is as follows: curcumin and lauric acid are weighed respectively and added into a dichloromethane / anhydrous ethanol mixed solution, wherein the volume ratio of dichloromethane to anhydrous ethanol is 4:1;
[0024] The mixing is preferably carried out under stirring conditions, more preferably under magnetic stirring conditions; the stirring rate is 300-400 rpm; the stirring time is 1-2 hours, and the final solution concentration is: curcumin 1% (w / v), lauric acid 20% (w / v);
[0025] The mixing is preferably carried out under stirring conditions, more preferably under magnetic stirring conditions; the stirring rate is 300 to 400 rpm;
[0026] The electrostatic spraying process of the curcumin / lauric acid spinning solution in step 4 is as follows: first, the curcumin / lauric acid solution is sucked into a 5mL syringe, and then the syringe is installed on the syringe pump, and the infusion rate is adjusted to 3mL / h. The above-mentioned flexible strain sensor layer is refixed on the metal collection plate, and the position is adjusted to align with the collection area of the electrostatic spraying. Then turn on the high-voltage DC power supply, adjust the voltage to 20kV, and start spraying. The needle is 15cm away from the collection plate and collected for 1h.
[0027] Compared with the prior art, the technical solution provided by the present invention has the following technical advantages:
[0028] 1. The technical solution provided by the present invention combines photothermal technology and phase change materials to build a photothermal drug controlled release platform, thereby accelerating wound repair through photothermal antibacterial and controlled release of curcumin. At the same time, the TPU nanofiber membrane is used to give the wound dressing high stretchability and high air permeability, and the integration of Peano-type liquid metal circuit channels gives the wound dressing the ability to convert tensile strain into electrical signals, thereby achieving motion management of skin wounds.
[0029] 2. The intelligent wound dressing with both photothermal drug controlled release and motion sensing monitoring functions provided by the present invention uses electrostatic spraying technology to load the drug curcumin and phase change material lauric acid onto the surface of the nanofiber membrane prepared by electrospinning, and at the same time in situ prints liquid metal in the double-layer nanofiber membrane to act as a photothermal agent and flexible circuit to achieve controlled release of curcumin to treat wounds through photothermal effect, while also being able to monitor the movement state of wounds at joints in real time.
[0030] 3. The intelligent wound dressing with both photothermal drug controlled release and motion sensing monitoring functions prepared by the present invention provides a feasible method for preparing wound dressings with both precise drug controlled release and monitoring functions, and also provides a new solution for the development of skin wound repair dressings at joints. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is the appearance picture of TPU@LM@CUR prepared in Example 1.
[0032] Figure 2 This is the microscopic morphology data diagram of TPU@LM@CUR prepared in Example 1.
[0033] Figure 3 This is the infrared spectrum of TPU@LM@CUR prepared in Example 1.
[0034] Figure 4 This is an EDS image of the liquid metal flexible circuit of the present invention.
[0035] Figure 5 This is the stress-strain curve of TPU@LM@CUR of the present invention.
[0036] Figure 6 This is a graph showing the water contact angle test results of each material group in the present invention;
[0037] Figure 7 It is a graph showing the experimental data of water vapor transmission rate of each material group in the present invention.
[0038] Figure 8 This is a thermal performance test diagram of the drug-loaded micron particles of the present invention.
[0039] Fig. 9 This is a photothermal performance test data diagram in the present invention.
[0040] Fig.10 It is a graph showing the results of an in vitro release test of curcumin of the present invention.
[0041] Fig.11 It is a graph showing the antibacterial activity test results of each group of materials of the present invention.
[0042] Fig.12 It is a graph showing the anti-inflammatory activity test results of each group of materials of the present invention.
[0043] Fig.13 It is a graph showing the antioxidant activity test results of each group of materials of the present invention.
[0044] Fig.14 This is a diagram of the sensor performance test results of the present invention. DETAILED DESCRIPTION
[0045] The present invention is further described in detail below by examples:
[0046] Example 1
[0047] This embodiment provides a smart wound dressing with both photothermal drug controlled release and motion sensing monitoring functions, which is prepared by the following steps in sequence:
[0048] S1) Preparation of TPU nanofiber membrane
[0049] (1) Preparation of TPU spinning solution: 0.375 g of TPU was added to 5 mL of hexafluoroisopropanol, mixed at room temperature, and stirred under magnetic stirring at a speed of 400 rpm for 6 h. Finally, a transparent TPU spinning solution with a concentration of 15% (w / v) was obtained.
[0050] (2) Preparation of nanofiber membrane by electrospinning: First, the TPU spinning solution was sucked into a 5 mL syringe, and then the syringe was installed on the syringe pump, and the spinning speed was adjusted to 1.5 mL / h. A piece of silicone oil paper was taken and pasted on a metal collecting plate; finally, the high-voltage DC power supply was turned on, the voltage was adjusted to 18 kV, and spinning began. The needle was 15 cm away from the collecting plate, and the collection was carried out for 2.5 h to obtain a TPU nanofiber membrane.
[0051] (3) The TPU nanofiber membrane is placed in a vacuum oven, dried at room temperature under vacuum conditions for 12 hours, and then cut into two pieces of TPU nanofiber membrane of the same size for later use.
[0052] S2) Preparation of TPU@LM
[0053] (1) Using a cutting machine, a Peano pattern was cut out on a PVC board as an in-situ stencil printing template, and the in-situ stencil printing template was placed on top of one of the TPU nanofiber membranes prepared in S1. Then, 99.999% pure EGaIn liquid metal (75wt% Ga, 25wt% In, and trace impurities of Sn) was in-situ stencil printed to obtain a flexible circuit layer TPU@LM.
[0054] (2) Encapsulation of flexible strain sensor layer:
[0055] Another piece of TPU nanofiber membrane is spun onto the surface of the flexible circuit layer TPU@LM liquid metal prepared in step (1) by electrospinning to obtain a flexible strain sensor layer named TPU@LM. The TPU@LM is placed in a vacuum oven and dried at room temperature for 12 hours under vacuum conditions before use.
[0056] S3) Preparation of initial TPU@LM@CUR
[0057] (1) Preparation of curcumin / lauric acid solution: 0.025 g of curcumin and 0.5 g of lauric acid were added to a mixed solution of 4 mL of dichloromethane and 1 mL of anhydrous ethanol, and stirred under magnetic stirring at a speed of 300 rpm for 2 h. Finally, a clear curcumin / lauric acid solution with a concentration of 1% (w / v) curcumin and 20% (w / v) lauric acid was obtained.
[0058] (3) Preparation of drug-loaded micronized particles by electrostatic spraying: First, the curcumin / lauric acid solution was sucked into a 5 mL syringe, and then the syringe was mounted on a syringe pump, and the infusion rate was adjusted to 3 mL / h. The TPU@LM prepared in S2 was re-fixed on a metal collecting plate, and the position was adjusted so that it was aligned with the collection area of the electrostatic spraying. Then, the high-voltage DC power supply was turned on, the voltage was adjusted to 20 kV, and spraying was started. The needle was 15 cm away from the roller, and the collection was carried out for 1 hour to obtain TPU@LM loaded with curcumin nanoparticles, which was named as the product TPU@LM@CUR.
[0059] (4) Place the TPU@LM@CUR in a vacuum oven and dry it at room temperature for 12 hours under vacuum conditions before use.
[0060] Example 2
[0061] This embodiment provides a smart wound dressing with both photothermal drug controlled release and motion sensing monitoring functions, which is prepared by the following steps in sequence:
[0062] S1) Preparation of TPU nanofiber membrane
[0063] (1) Preparation of TPU spinning solution: 0.75 g of TPU was added to 5 mL of hexafluoroisopropanol, mixed at room temperature, and stirred under magnetic stirring at a speed of 400 rpm for 12 h. Finally, a transparent TPU spinning solution with a concentration of 15% (w / v) was obtained.
[0064] (2) Preparation of nanofiber membrane by electrospinning: First, the TPU spinning solution was sucked into a 5 mL syringe, and then the syringe was installed on the syringe pump, and the spinning speed was adjusted to 1.5 mL / h. A piece of silicone oil paper was taken and pasted on a metal collecting plate; finally, the high-voltage DC power supply was turned on, the voltage was adjusted to 19 kV, and spinning began. The needle was 15 cm away from the collecting plate, and the collection was carried out for 2.5 h to obtain a TPU nanofiber membrane.
[0065] (3) The TPU nanofiber membrane is placed in a vacuum oven, dried at room temperature under vacuum conditions for 12 hours, and then cut into two pieces of TPU nanofiber membrane of the same size for later use.
[0066] S2) Preparation of TPU@LM
[0067] (1) Using a cutting machine, a Peano pattern was cut out on a PVC board as an in-situ stencil printing template, and the in-situ stencil printing template was placed on top of one of the TPU nanofiber membranes prepared in S1. Then, 99.999% pure EGaIn liquid metal (75wt% Ga, 25wt% In, and trace impurities of Sn) was in-situ stencil printed to obtain a flexible circuit layer TPU@LM.
[0068] (2) Encapsulation of flexible strain sensor layer:
[0069] Another piece of TPU nanofiber membrane is spun onto the surface of the flexible circuit layer TPU@LM liquid metal prepared in step (1) by electrospinning to obtain a flexible strain sensor layer named TPU@LM. The TPU@LM is placed in a vacuum oven and dried at room temperature for 12 hours under vacuum conditions before use.
[0070] (1) Preparation of curcumin / lauric acid solution: 0.05 g of curcumin and 1 g of lauric acid were added to a mixed solution of 4 mL of dichloromethane and 1 mL of anhydrous ethanol, and stirred under magnetic stirring at a speed of 300 to 400 rpm for 1 to 2 h. Finally, a clear curcumin / lauric acid solution was obtained with a concentration of 1% (w / v) curcumin and 20% (w / v) lauric acid.
[0071] (3) Preparation of drug-loaded micronized particles by electrostatic spraying: First, the curcumin / lauric acid solution was sucked into a 5 mL syringe, and then the syringe was mounted on a syringe pump, and the infusion rate was adjusted to 3 mL / h. The TPU@LM prepared in S2 was re-fixed on a metal collecting plate, and the position was adjusted so that it was aligned with the collection area of the electrostatic spraying. Then, the high-voltage DC power supply was turned on, the voltage was adjusted to 20 kV, and spraying was started. The needle was 15 cm away from the roller, and the collection was carried out for 1 hour to obtain TPU@LM loaded with curcumin nanoparticles, which was named as the product TPU@LM@CUR.
[0072] (4) Place the TPU@LM@CUR in a vacuum oven and dry it at room temperature for 12 hours under vacuum conditions before use.
[0073] Example 3
[0074] This embodiment provides a smart wound dressing with both photothermal drug controlled release and motion sensing monitoring functions, which is prepared by the following steps in sequence:
[0075] S1) Preparation of TPU nanofiber membrane
[0076] (1) Preparation of TPU spinning solution: 1.125 g of TPU was added to 5 mL of hexafluoroisopropanol, mixed at room temperature, and stirred under magnetic stirring at a speed of 350 rpm for 9 h. Finally, a transparent TPU spinning solution with a concentration of 15% (w / v) was obtained.
[0077] (2) Preparation of nanofiber membrane by electrospinning: First, the TPU spinning solution was sucked into a 5 mL syringe, and then the syringe was installed on the syringe pump, and the spinning speed was adjusted to 1.5 mL / h. A piece of silicone oil paper was taken and pasted on a metal collecting plate; finally, the high-voltage DC power supply was turned on, the voltage was adjusted to 18 kV, and spinning began. The needle was 15 cm away from the collecting plate, and the collection was carried out for 2.5 h to obtain a TPU nanofiber membrane.
[0078] (3) The TPU nanofiber membrane is placed in a vacuum oven, dried at room temperature under vacuum conditions for 12 hours, and then cut into two pieces of TPU nanofiber membrane of the same size for later use.
[0079] S2) Preparation of TPU@LM
[0080] (1) Using a cutting machine, a Peano pattern was cut out on a PVC board as an in-situ stencil printing template, and the in-situ stencil printing template was placed on top of one of the TPU nanofiber membranes prepared in S1. Then, 99.999% pure EGaIn liquid metal (75wt% Ga, 25wt% In, and trace impurities of Sn) was in-situ stencil printed to obtain a flexible circuit layer TPU@LM.
[0081] (2) Encapsulation of flexible strain sensor layer:
[0082] Another piece of TPU nanofiber membrane is spun onto the surface of the flexible circuit layer TPU@LM liquid metal prepared in step (1) by electrospinning to obtain a flexible strain sensor layer named TPU@LM. The TPU@LM is placed in a vacuum oven and dried at room temperature for 12 hours under vacuum conditions before use.
[0083] S3) Preparation of initial TPU@LM@CUR
[0084] (1) Preparation of curcumin / lauric acid solution: 0.75 g of curcumin and 1.5 g of lauric acid were added to a mixed solution of 4 mL of dichloromethane and 1 mL of anhydrous ethanol, and stirred under magnetic stirring at a speed of 300 to 400 rpm for 1 to 2 h. Finally, a clear curcumin / lauric acid solution was obtained with a concentration of 1% (w / v) curcumin and 20% (w / v) lauric acid.
[0085] (3) Preparation of drug-loaded micronized particles by electrostatic spraying: First, the curcumin / lauric acid solution was sucked into a 5 mL syringe, and then the syringe was mounted on a syringe pump, and the infusion rate was adjusted to 3 mL / h. The TPU@LM prepared in S2 was re-fixed on a metal collecting plate, and the position was adjusted so that it was aligned with the collection area of the electrostatic spraying. Then, the high-voltage DC power supply was turned on, the voltage was adjusted to 20 kV, and spraying was started. The needle was 15 cm away from the roller, and the collection was carried out for 1 hour to obtain TPU@LM loaded with curcumin nanoparticles, which was named as the product TPU@LM@CUR.
[0086] (4) Place the TPU@LM@CUR in a vacuum oven and dry it at room temperature for 12 hours under vacuum conditions before use.
[0087] In order to demonstrate the advantages of the technical solution provided by this application, the TPU@LM@CUR detection experiment provided by this application is given below:
[0088] Test 1
[0089] The surface morphology of each part of the TPU@LM@CUR prepared in Example 1 was observed by scanning electron microscopy. Figure 1 , see the microscopic morphology data diagram Figure 2 , as follows:
[0090] First, the TPU fiber membrane, TPU@LM and TPU@LM@CUR were respectively taped to the metal platform. Then, the diameter of 50 nanofiber membranes was measured using ImageJ software to obtain the diameter and frequency distribution of the fibers. Figure 1 As shown; the surface morphology of TPU nanofibers is as Figure 2 (ab) As shown. The SEM images show that the surface of the nanofibers prepared in this application is uniform and continuous, and the diameter of the fiber is 797.50±99.53nm, indicating that the electrospinning technology we used can effectively control the structural size and shape of the fiber. The surface morphology of CURNPs is shown in Figure 2 (c) shows that the diameter of CURNPs is 481.61±180.61nm. It is closely combined with TPU nanofibers because of the presence of residual solvent in the electrostatic spraying process, and the electrosprayed particles can adhere firmly to the fibers. The surface morphology of the connection between the liquid metal circuit pattern and the nanofiber membrane is shown in Figure 2. Figure 2 (d) is shown. It is particularly noted that the liquid metal circuit is evenly covered on the fiber surface and the edge of the circuit is relatively smooth. The uniformity and smoothness of the liquid metal circuit can ensure the consistency of electrical properties. The above results show that we have prepared TPU nanofibers and CURNPs particles with good morphology through electrospinning technology and electrostatic spraying technology, and successfully printed the liquid metal circuit on the nanofiber membrane.
[0091] In order to confirm the successful preparation of CURNPs and TPU@LM@CUR, the chemical functional groups of each part were characterized by Fourier transform infrared spectroscopy with a detection band of 400–4000 cm -1 At the same time, the TPU@LM was tested for gallium, indium and tin elements using the EDS mode of a scanning electron microscope.
[0092] In order to further prove the successful preparation of TPU@LM@CUR, this application used Fourier transform infrared spectroscopy to analyze the samples ( Figure 3 ). In the infrared spectrum of CURNPs, we observed that -1 The characteristic peaks of carboxyl group near 1503 cm -1 The characteristic peak of the double bond of the benzene ring is due to the successful mixing of curcumin and lauric acid by electrostatic spraying technology and the preparation of drug-loaded particles. TPU, TPU@LM and TPU@LM@CUR all have similar infrared spectra. TPU@LM@CUR has a peak at 2700cm -1 ~3000cm -1 The same ethyl groups as those of CURNPs appeared in the range, which proved that CURNPs were successfully composited onto the nanofiber membrane by electrostatic spraying technology. EDS image ( Figure 4 ) It can be seen that the liquid metal used in this application is mainly composed of gallium and indium elements, and the distribution of each element is uniform. These results all show that this application successfully prepared TPU@LM@CUR.
[0093] Test 2 Mechanical properties test
[0094] In order to test the mechanical properties of TPU@LM@CUR, a universal tensile testing machine was used for testing. First, the thickness of TPU@LM@CUR was measured with a vernier caliper, and then it was vertically fixed on the universal tensile testing machine and stretched at a rate of 30mm / min to obtain the stress-strain curve of TPU@LM@CUR. Figure 5 This is the stress-strain curve of TPU@LM@CUR, which shows an elongation at break of up to 434.13%, proving that it has excellent mechanical properties and can be used as wound dressing and flexible electronic materials.
[0095] Test 3 Water contact angle test
[0096] In order to verify the hydrophilicity and hydrophobicity of TPU@LM@CUR, an optical contact angle meter was used for testing. First, the material was fixed on a glass slide, and 5 μL of deionized water was dripped onto the surface of the nanofiber membrane by controlling the syringe to measure the water contact angle. The experiment was repeated three times.
[0097] The water contact angles of each material group in this study are as follows Figure 6 As shown in the figure, the water contact angles of TPU, TPU@LM and TPU@LM@CUR are 134.37°±0.70°, 132.73°±1.95° and 103.57°±1.79°, respectively, all of which have excellent hydrophobicity. The water contact angle of TPU@LM@CUR decreased by about 30° after the addition of CURNPs. Although curcumin in the microparticles is also hydrophobic, the oxygen in its chemical structure is a proton donor and can bind to water. Therefore, after the addition of curcumin, the hydrophilicity of the nanofibers is slightly enhanced and the contact angle decreases. The hydrophobicity of the TPU nanofiber membrane ensures the waterproof ability of the flexible strain sensor, so that the flexible strain sensor can work normally under the condition of wound exudate. In addition, the hydrophobic TPU nanofibers are conducive to the removal of the dressing from the wound, avoiding secondary damage to the wound. The low hydrophilicity of TPU also helps to prevent microorganisms from contacting and adhering to the wound dressing, thereby achieving an auxiliary antibacterial effect.
[0098] Test 4 Water vapor transmission rate test
[0099] Different materials were fixedly wrapped at the opening of a glass test tube containing 5 mL of deionized water, and the glass test tube without material wrapping was used as a blank group. Then all glass test tubes were placed in a desiccator at 24.8°C and 29% relative humidity for 24 hours, and the weight of the glass test tubes before and after 24 hours was recorded. The water vapor transmission rate was calculated as follows:
[0100]
[0101] Where W0 is the initial weight of the glass test tube, W tis the final weight of the glass test tube, and A is the area of the mouth of the glass test tube.
[0102] like Figure 7 As shown in Figure 2, the water vapor transmission rates of Single-TPU, Double-TPU, TPU@CUR, TPU@LM and TPU@LM@CUR are 493.96±5.32g / m 2 / day、489.41±10.86g / m 2 / day、496.56±7.03g / m 2 / day、498.51±5.55g / m 2 / day and 472.72±6.76g / m 2 / day. According to previous literature reports, the water vapor permeability of effective wound dressings should be between 76.00 and 9360.00 g / m 2 / day. Too high a water vapor permeability will lead to faster drying of the wound and scar formation, while a lower water vapor permeability will lead to accumulation of exudate, which may cause bacterial growth and delayed healing. In addition, literature reports that the water vapor permeability of normal human skin is about 204.00 g / m 2 / day, while the water vapor transmission rate of commercial wound dressing (Bioclusive - from Johnson & Johnson) is only 393.60g / m 2 / day, TPU@LM@CUR has a better water vapor permeability than commercial wound dressings. In this study, the water vapor permeability of TPU@LM@CUR was slightly reduced compared with the blank group, which may be due to the addition of curcumin. The oxygen contained in the curcumin structure is a proton donor and can bind to water.
[0103] Test 5 Thermal performance test
[0104] In order to verify the phase transition temperature of CURNPs, differential scanning calorimeter (DSC) was used for testing. The specific test conditions are as follows: in an argon atmosphere, the temperature range is 0℃~80℃, the heating and cooling rate is 5℃ / min, and the gas flow rate is 20mL / min.
[0105] The results are as follows Figure 8 As shown in the figure, the melting temperatures (Tm) of pure LA and CURNPs are around 43.4°C and 42.6°C, respectively. The DSC curves of pure LA and CURNPs are almost the same, which further proves that LA and CUR are successfully blended. The temperature drops slightly after adding CUR, which is because the blending of CUR and LA will destroy the LA crystal structure and make the bonds between the crystal particles fragile, which in turn leads to a decrease in the melting temperature of LA.
[0106] Test 6: Photothermal performance test
[0107] TPU, TPU@LM and TPU@LM@CUR were placed in 24-well plates, and 2 mL of PBS buffer solution was added to each well. They were irradiated with an 808 nm near-infrared laser at a distance of 2 cm and a power density of 1.71 W / cm 2 , irradiate for 15 minutes. And use an infrared thermal imager to record the temperature every 30 seconds. Fig. 9 (ab) The results show that at 1.71W / cm 2 After irradiation for 15 minutes at a power density of 1.5 ℃, the temperature of TPU@LM and TPU@LM@CUR can rise to about 45℃, while the temperature of pure TPU has no obvious change. From the above experimental results, it can be seen that the melting temperature of CURNPs is 42.6℃, and 45℃ is enough to release CUR from the micron particles to achieve the effect of photothermal controlled release of drugs. At the same time, the photothermal stability of TPU@LM and TPU@LM@CUR was investigated by turning on / off laser irradiation. The results are as follows Fig. 9 As shown in (cd), the temperature level maintained by the dressing after four near-infrared laser irradiations is similar to that of the first near-infrared laser irradiation, indicating that it has good photothermal repeatability and stability. The photothermal performance results of TPU@LM and TPU@LM@CUR show that the wound dressing still has excellent photothermal performance after adding CURNPs.
[0108] Test 7 verifies the drug controlled release performance of the prepared smart wound dressing through in vitro release detection of curcumin.
[0109] The specific steps are:
[0110] (1) TPU@LM@CUR was placed in a 24-well plate, and 2 mL of PBS buffer solution was added to each well. An 808 nm near-infrared laser was used at 1.71 W / cm 2 The power density was irradiated at a distance of 2 cm for 15 min. After irradiation, the supernatant of each sample was collected and immediately supplemented with 2 mL of fresh PBS solution. Next, the 24-well plate was left to stand for 15 min, and the supernatant of each sample was collected after the end. The above operation was repeated 4 times.
[0111] (2) Finally, use an ultraviolet spectrophotometer to measure the absorbance of the collected supernatant at a wavelength of 422 nm.
[0112] (3) Establish a CUR standard curve (y = 0.145x + 0.0103,
[0113] R 2 =0.9981).
[0114] (4) The experiment was repeated three times, the experimental data were processed, and the cumulative release of CUR was calculated.
[0115] The results are as follows Fig.10 As shown in (a), the drug release rate obviously increases under the condition of 45°C. Fig.10 As shown in (b), under laser irradiation, the drug showed rapid release, and under room temperature, the drug showed negligible release. Subsequently, based on the release curve results of CUR, the drug release amount per unit time was calculated. The results are shown in Fig.10 As shown in (c), the maximum CUR release was observed after the first near-infrared laser irradiation, and the CUR release after the near-infrared laser irradiation in the four cycles was significantly higher than that without near-infrared laser irradiation. The above experimental results prove that the present application successfully prepared a wound dressing capable of photothermal controlled drug release.
[0116] Test 8
[0117] The inhibition rate of each material group obtained in Example 1 against Escherichia coli and Staphylococcus aureus was evaluated by antibacterial experiments to verify its antibacterial activity. The specific steps are:
[0118] (1) Bacterial resuscitation: First, take out the bacterial solution from the -80°C refrigerator and thaw it. After the bacterial solution is completely thawed, take 50 μL of the bacterial solution and drop it on the nutrient agar. Place it in an incubator at 37°C and culture it for 12 h.
[0119] (2) Extraction of strains: Use an inoculation loop to scrape the strains and add them to sterilized physiological saline, and use a pipette to blow and mix them evenly to obtain a bacterial solution with an optical density of 0.09 to 0.1 at a wavelength of 620 nm on an ELISA reader, thereby obtaining 1.5×10 8 CFU / mL concentration of bacterial suspension. The bacterial suspension was then further diluted to 1.5×10 5 CFU / mL.
[0120] (3) Each group of materials was placed in a 24-well plate, and 2 mL of bacterial suspension was added to each well. An 808 nm near-infrared laser was used at 1.71 W / cm 2 The material was irradiated with a power density of 2 cm for 15 min. The blank control group was only added with bacterial suspension and was not photothermally treated as a non-photothermally treated control. After the treatment, the 24-well plate was placed in a constant temperature incubator at 37 ° C for 4 h.
[0121] (4) After 4 hours, dilute the bacterial solution in the 24-well plate with physiological saline. Finally, take 50 μL of the diluted bacterial solution and spread it on the nutrient agar with a glass spreading rod. After culturing in a constant temperature incubator at 37°C for 12 hours, observe the culture dish and count the number of colonies.
[0122] The experimental results are as follows Fig.11 As shown in the figure, the colony counts of Escherichia coli and Staphylococcus aureus in the TPU@CUR group and TPU@LM@CUR group without near-infrared laser irradiation were reduced compared with the blank group without near-infrared laser irradiation, and the TPU@LM@CUR group showed a lower colony count. This is because the CUR on the surface of CURNPs that is not wrapped inside the structure directly contacts the bacteria in the solution, causing the bacteria to die. In addition, the liquid metal of TPU@LM@CUR contains G a3+ , which can interfere with the normal metabolism of Fe3+ in biological systems, thereby inhibiting the proliferation of bacteria. In the TPU@LM group and TPU@LM@CUR group, near-infrared laser treatment showed higher antibacterial ability. This is because liquid metal, as a photothermal agent, can raise the temperature to 45°C under near-infrared irradiation, which can destroy the internal structure of some bacteria and accelerate the release of CUR in TPU@LM@CUR, achieving a rapid antibacterial effect. The results show that due to the synergistic effect of photothermal effect and CUR release, TPU@LM@CUR has good antibacterial activity.
[0123] Test 9
[0124] The anti-inflammatory activity test was used to evaluate the effects of each material group on the inflammatory response of RAW 264.7 cells induced by lipopolysaccharide (LPS) to verify its anti-inflammatory activity. The specific steps are as follows:
[0125] (1) Add 5 × 10 4 The cells were placed in a cell culture incubator at 37°C and 5% CO2 for 24 h.
[0126] (2) Each group of materials was cut into a size of 30 × 30 mm, placed in a 24-well plate, and then subjected to UV irradiation for 30 min.
[0127] (3) Then, 2 mL of complete culture medium was added to each well and the extract was obtained after soaking for 2 h. The blank control group was only added with complete culture medium. The NIR group was first illuminated with a near-infrared laser at 1.71 W / cm 2 The cells were irradiated with a power density of 100 μg / cm2 for 15 min, and then immersed for 1 h 45 min under the same conditions as the other groups. After the immersion, the complete medium and the obtained extract were diluted in a ratio of 2:1 to obtain the desired conditioned medium.
[0128] (4) After culturing for 24 hours, discard the old cell culture medium in the 96-well plate, add 100 μL of LPS solution to each well to stimulate NO production, and place in the incubator for 2 hours. Then, add 100 μL of the corresponding conditioned medium to each well, and then continue to culture in the incubator for 24 hours.
[0129] (5) After 24 h of incubation, 100 μL of supernatant from each well was mixed with 100 μL of nitric oxide detection reagent (Griess reagent) and added to another 96-well plate. The plate was kept in the dark for 15 min, and the optical density was measured at a wavelength of 540 nm using an ELISA reader to calculate the NO inhibition rate.
[0130] The results are as follows Fig.12 As shown in (ab), compared with the positive control group treated with LPS only, the OD values of the TPU group, TPU@LM group, and TPU@CUR group did not decrease significantly, proving that they all had no anti-inflammatory ability. However, in the TPU@LM@CUR group, the near-infrared laser treatment showed a lower OD value, and its inhibition rate on NO was calculated to be 57.68%. The inverted microscope images of RAW 264.7 cells after treatment are shown in Figure 2. Fig.12 As shown in (c), the cells in the negative control group treated with complete medium only showed regular round or oval shapes, while the macrophages stimulated with LPS extended longer pseudopodia and showed irregular shapes. The cell morphology of the TPU@LM@CUR group treated with near-infrared laser was the same as that of the negative control group, with only a few showing irregular shapes. The above experimental results show that under near-infrared laser treatment, the LA of TPU@LM@CUR melted from solid to liquid, resulting in a large amount of CUR release, thereby enhancing its anti-inflammatory activity.
[0131] Test 10
[0132] The DPPH scavenging method was used to evaluate the antioxidant properties of each material group. The specific steps are:
[0133] (1) Cut each group of materials into a size of 30×30 mm, place them in a 24-well plate, and add 2 mL of PBS buffer to each well.
[0134] (2) The photothermal group used a near-infrared laser at 1.71 W / cm 2 The cells were irradiated with a power density of 100 nm for 15 min, the non-photothermal group was left to stand for 15 min, and the blank control group was only given PBS buffer.
[0135] (3) After the treatment, 1 mL of supernatant from each group was collected and mixed evenly with 1 mL of DPPH ethanol solution (0.1 mM), and incubated in the dark at room temperature for 30 min.
[0136] (4) After the incubation, the absorbance of the solution was measured at 517 nm using a UV-visible photometer.
[0137] (5) In order to determine the change of antioxidant activity of TPU@LM@CUR with photothermal time, a near-infrared laser was used at 1.71 W / cm 2The power density was irradiated for 0, 5, 10, and 15 min. The supernatant was extracted at each time point and mixed with DPPH ethanol solution to react, and the absorbance of the corresponding solution at 517 nm was measured. The experiment was repeated 3 times.
[0138] (6) Antioxidant activity was evaluated using the following formula:
[0139]
[0140] Among them A control is the absorbance of the blank control group, A sample is the absorbance of each material group
[0141] The results are as follows Fig.13 As shown in (ab), the color of the solutions of the TPU group and the TPU@LM group remained unchanged after 30 minutes of reaction with the DPPH solution, with or without near-infrared laser irradiation. However, in the TPU@LM@CUR group, the color of the solution changed from purple to yellow after reaction with the DPPH solution, proving that the combination of TPU@LM@CUR and near-infrared laser irradiation has a strong antioxidant capacity, and its free radical scavenging efficiency was calculated to be 68.42%. In order to verify the relationship between the near-infrared laser irradiation treatment time and the antioxidant capacity of the TPU@LM@CUR group, the applicant collected solutions treated with near-infrared laser irradiation at different time points and reacted with DPPH solution, and calculated the free radical scavenging rates respectively. The results are shown in Fig.13 As shown in (cd), with the increase of near-infrared laser irradiation treatment time, the antioxidant capacity of the TPU@LM@CUR group gradually increased.
[0142] Since the tensile tests of the stretchable strain sensors provided in this application are all carried out using a programmable tensile testing machine. The resistance signal of the sensor is collected using a resistor meter. Including the strain sensitivity (GF) of the flexible strain sensor, the cyclic strain sensing behavior under different tensile strains, and the cyclic stability of the flexible sensor under a constant 20% strain. By connecting the flexible sensor to healthy volunteers and monitoring the bending degree of their joints (wrist, fingers, elbow, knee), the resistor meter can clearly display its real-time resistance changes under various activity states. By connecting the power supply equipment, LED bulbs and flexible strain sensors in series, a harmful deformation alarm model is prepared.
Claims
1. An intelligent wound dressing with both drug controlled release and motion detection functions, characterized in that: It consists of a base material, a photothermal agent and a sensor flexible agent liquid metal, a drug-carrying phase change material lauric acid and an active component curcumin.
2. The smart wound dressing with both drug controlled release and motion detection functions according to claim 1, characterized in that: The base material is thermoplastic polyurethane.
3. The smart wound dressing with both drug controlled release and motion detection functions according to claim 1, characterized in that: The liquid metal is eutectic gallium-indium with a purity of 99.999%, wherein the gallium content is 75wt% and the In content is 25wt%.
4. The smart wound dressing with both drug controlled release and motion detection functions according to claim 1, characterized in that: The mass ratio of the base material, lauric acid and curcumin is 75-225:50-150:2.5-7.
5.
5. The method for preparing the smart wound dressing with both drug controlled release and motion detection functions according to claim 1, characterized in that: The steps are as follows: S1: electrospinning the TPU spinning solution to obtain a TPU nanofiber membrane, and cutting it into two pieces of the same size for standby use; S2: A Peano pattern is printed on one of the TPU nanofiber membranes prepared in S1 through an in-situ template, and liquid metal is filled in the hollow part of the Peano pattern to obtain a TPU nanofiber membrane with a flexible circuit; S3: Another piece of TPU nanofiber membrane prepared in S1 was bonded to the TPU nanofiber membrane with flexible circuit prepared in S2 printed with liquid metal surface by electrospinning to obtain a flexible strain sensor layer, named TPU@LM; S4: The curcumin / lauric acid solution is bonded to the TPU@LM prepared in S2 by electrostatic spraying to obtain the primary product TPU@LM@CUR; Step 5: With the liquid metal circuit Peano pattern as the center, cut the TPU@LM@CUR prepared by S4 to obtain the finished smart wound dressing TPU@LM@CUR.
6. The method for preparing the intelligent wound dressing with both drug controlled release and motion detection functions according to claim 5, characterized in that: The TPU nanofiber membrane is prepared by the following method: (1) adding TPU to hexafluoroisopropanol, mixing at room temperature, stirring under magnetic stirring for 6 to 12 hours, and finally clarifying to obtain a transparent TPU spinning solution with a concentration of 15 w / v%; (2) The TPU spinning solution prepared in step (1) is sucked into a syringe and sprayed onto a metal collecting plate pasted with silicone oil paper to obtain a TPU nanofiber membrane.
7. The method for preparing the intelligent wound dressing with both drug controlled release and motion detection functions according to claim 6, characterized in that: Step (2) is specifically as follows: first, the TPU spinning solution is sucked into a 5 mL syringe, and then the syringe is installed on the syringe pump, and the spinning speed is adjusted to 1.5 mL / h; then the silicone oil paper is pasted on the metal collecting plate; finally, the high-voltage DC power supply is turned on, the voltage is adjusted to 18-19 kV, the needle is 15 cm away from the collecting plate, spinning is started, and the collection time is 2.5 h to obtain a TPU nanofiber membrane.
8. The method for preparing the smart wound dressing with both drug controlled release and motion detection functions according to claim 5, characterized in that: The TPU@LM loaded with curcumin nanoparticles is prepared by the following method: (1) adding curcumin and lauric acid to the mixed solution, stirring for 1 to 2 hours under magnetic stirring, and finally clarifying to obtain a transparent curcumin / lauric acid solution, wherein the curcumin concentration is 1 w / v% and the lauric acid concentration is 20 w / v%; (2) The curcumin / lauric acid solution prepared in step (1) was sucked into a syringe, and then the syringe was installed on a syringe pump, and the infusion rate was adjusted to 3 mL / h. The TPU@LM was fixed on a metal collecting plate, and the position was adjusted so that it was aligned with the collection area of the electrostatic spraying. Then, the high-voltage DC power supply was turned on, the voltage was adjusted to 20 kV, the needle was 15 cm away from the roller, and spraying was started. The collection was performed for 1 hour to obtain TPU@LM loaded with curcumin nanoparticles.
9. The method for preparing the intelligent wound dressing with both drug controlled release and motion detection functions according to claim 8, characterized in that: The mixed solution consists of dichloromethane and anhydrous ethanol in a volume ratio of 4:
1.
10. The method for preparing the smart wound dressing with both drug controlled release and motion detection functions according to claim 5, characterized in that: The flexible circuit is a Peano type liquid metal strain sensing circuit.
11. The smart wound dressing with both drug controlled release and motion detection functions according to any one of claims 1 to 4 is used as a drug for treating wound healing, or as an instrument for detecting the degree of flexion and extension of human joints.
Citation Information
Cited By
Intelligent effect evaluation method for curcumin composite fiber wound dressing
CN121331472A
Near-infrared-triggered phase-change controlled-release low-temperature photo-thermal synergistic nano-particles as well as preparation and application thereof
CN122163797A